Caring Ability of Postcaesarean Mothers and Itâs Association with Cultural Value - Hodikoh, Atik; Setyowati, Setyowati (Universitas Airlangga, 2015)
Introduction: Ability to care ofÂ postcaesarean mother affected by multifactor; moternalÂ characteristic, knowledge and cultural values. Postcaesarean mother has high level of dependency in performing selfcare and baby care. The aim of this study wasÂ toÂ identifiedÂ of selfcare and baby care and relation with that factorsÂ and cultural behaviour associaated pospartum care. Method: this study used cross sectional design with a purpossive sampling of 66 post caesarean mother ini five hospital in West Java. Instrumen used consisted ofÂ maternalÂ characteristic including ages, parity,job, income, knowledga,Â cultural values, cultural behaviourÂ and observasional instruments ofÂ the ability to care. Result: there was a significant relationship between job characteristic and cultural values with the ability to care, for the correlation r 0.295 an 0.355 (p value = 0.003). Discussion: nurses must perform a cultural approach in facilitating the mother to care for themselves and care for the baby in accordance with their cultural values, so that the mother can perform optimally care. Keywords: ability to, cultural values, job, postcaesarean care